A study to assess the psychosocial needs of patient family members in the intensive care unit - Lalthlanawmi Renthlei; Ronur Srikantasastry Ramesh; Mahalakshmy Thulasingam; Manjini Jeyaram Kumari (Acute and Critical Care)
Background Admission to an intensive care unit (ICU) is considered a mental crisis for patients and their families as they are unprepared for such a stressful and difficult situation. Hence, the objectives of this study are to assess the psychosocial needs of patient family members in the ICU in various dimensions such as assurance, proximity, information, support, and comfort; and to associate their psychosocial needs with their socio-demographic variables and clinical variables of the patient. Methods This was a cross-sectional analytical study conducted between December 2021 and January 2022 among 188 family members of patients admitted to the ICU using a convenience sampling technique in a tertiary hospital in Puducherry, India. The modified Critical Care Family Needs Inventory (CCFNI) questionnaire was administered to all consenting family members to determine their needs. Results The overall most important need among the five dimensions of modified CCFNI scores identified by the family members is the need for assurance (2.71±0.38). Using analysis of variance, statistical significances were found as follows. Education and comfort (F-statistic and P-value): 2.76 (0.029); relationship with the patient and assurance: 2.61 (0.036); relationship with the patient and support: 2.44 (0.048); level of consciousness and comfort: 4.63 (0.010); ICU visit restriction and assurance: 3.28 (0.022); ICU visit restriction and comfort: 8.08 (<0.001). Conclusion Since family members are essential members of the treatment teams, nurses should concentrate on reassuring them, assisting them in emerging from crises through appropriate communication, offering support, and attending to their needs.